Assessing The Competency Level Of Graduate Students: : A Gender Perspective - Neethu B Nair; Saravanan Raj; S. Raahalya (Journal of Agricultural Extension Management, 2026)
This study assesses competency levels among graduate students in agriculture, horticulture, and forestry disciplines in various states of India from a gender perspective. A total of 402 student respondents participated, with 215 responders through a Google forms survey and 187 from training programs organized by the National Institute of Agricultural Extension Management (MANAGE), Hyderabad. Competency was evaluated across four key constructs: cognitive, interpersonal, self-leadership, and digital, using a 13-group competency framework. Results indicated that while students demonstrated strengths in areas like self-leadership and interpersonal skills, significant gaps were found in digital competencies and certain cognitive skills. Gender-based analysis using the Mann-Whitney Test revealed that male students outperformed female students in critical thinking, mental flexibility, entrepreneurship, goal achievement, and digital skills. However, no significant gender differences were observed in planning, communication, teamwork, or self-awareness. The findings underscore the need for targeted educational interventions to bridge these competency gaps and enhance employability among graduates in the agricultural sector